Understanding the dynamics and conceptualization of environmental citizenship and energy citizenship: Evidence from the existing literature - Biresselioglu, Mehmet Efe; Demir, Muhittin Hakan; Solak, Berfu; Turan, Ugur (Frontiers in Energy Research, 2022)
This study seeks to better understand the relationships between environmental citizenship, energy citizenship, and related phenomena and the theoretical development and operationalization processes of environmental citizenship and energy citizenship in the path towards the energy transition and climate change mitigation through a bibliometric analysis. Doing so first provides an overview of how these concepts are defined in the literature establishes the frameworks for environmental citizenship and energy citizenship, including the characteristics, drivers, and pathways to their operationalization. The subsequent bibliometric analysis is conducted via the VOSviewer software, with more than 1,300 titles from the Web of Science database published between 1992 and 2021. The search keywords are “environmental citizenship” and “energy citizenship”. The results from the analysis highlight the terms sustainability and behaviour as the overarching concepts and common points of discussion regarding environmental citizenship and energy citizenship. Moreover, although environmental citizenship preserves its central position in the scholarly debate, there is a shift towards the phenomenon of energy citizenship and a set of emerging themes including “justice”, “energy democracy”, and “sustainable development”.